The Association of the Parent–Child Language Acculturation Gap with Obesity and Cardiometabolic Risk in Hispanic/Latino Youth: Results from the Hispanic Community Children’s Health Study/Study of Latino Youth (SOL Youth) - LeCroy, Madison N (Ann Behav Med, 2021)
BACKGROUND: Hispanic/Latino youth are disproportionately burdened by obesity and have a high prevalence of prediabetes and dyslipidemia. Differences in parent and child acculturation related to language use and preference (i.e., language acculturation) are associated with adverse cardiometabolic health behaviors, but no study has examined associations with cardiometabolic markers. PURPOSE: To determine whether discordance in parent–child language acculturation (parent–child acculturation gap) was associated with poor youth cardiometabolic health. METHODS: Hispanic/Latino 8–16-year-olds (n = 1,466) and parents from the Hispanic Community Children’s Health Study/Study of Latino Youth (SOL Youth) were examined. Mean scores for the Brief ARSMA-II’s Anglo (AOS) and Latino (LOS) Orientation Scales represented language acculturation. Cardiometabolic markers included youth body mass index (BMI) percentile, blood pressure percentiles, and dysglycemia and hyperlipidemia measures. Missing data were imputed. Survey-weighted multivariable linear regression examined the association of youth, parent, and youth × parent (the acculturation gap) AOS and LOS scores separately with each cardiometabolic marker. RESULTS: Youth reported greater English and lower Spanish use than parents. Greater discordance in AOS scores was associated with elevated BMI percentile only (p-for-interaction < .01). The LOS acculturation gap was not associated with any outcome. Adjustment for acculturative stress, family functioning and closeness, parenting style, and youth’s diet and physical activity did not alter findings. Removal of nonsignificant acculturation gaps did not indicate an association between individual youth or parent AOS or LOS scores and any cardiometabolic marker. CONCLUSIONS: Discordance in Hispanic/Latino parent–child dyads’ English use may relate to increased risk for childhood obesity. Future studies should identify mediators of this association.